2014
DOI: 10.5334/tohm.212
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Kinesigenic Dyskinesia Caused by 16p11.2 Microdeletion

Abstract: Background: Four cases of paroxysmal kinesigenic dyskinesia (PKD) have been reported in individuals with proximal 16p11.2 microdeletions that include PRRT2.Case Report: We describe a fifth patient with PKD, features of Asperger's syndrome, and mild language delays. Sanger sequencing of the PRRT2 gene did not identify any mutations implicated in PKD. However, microarray-based comparative genomic hybridization (aCGH) detected a 533.9-kb deletion on chromosome 16, encompassing over 20 genes and transcripts.Discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
(20 reference statements)
2
11
0
Order By: Relevance
“…Two of the patients (#58 and #81) were with DD/ID and one patient (#78) hasn’t shown DD/ID (<4 years-old). Our results are consistent with the previous reported ( Ebrahimi-Fakhari et al, 1993 ; Termsarasab et al, 2014 ). Ebrahimi-Fakhari et al (1993) reported that the patients with PRRT2 heterogenous variants commonly exhibited epilepsy and paroxysmal movement disorders (PRRT2-associated paroxysmal movement disorders, RRT2-PxMD) without intellectual delay.…”
Section: Discussionsupporting
confidence: 94%
“…Two of the patients (#58 and #81) were with DD/ID and one patient (#78) hasn’t shown DD/ID (<4 years-old). Our results are consistent with the previous reported ( Ebrahimi-Fakhari et al, 1993 ; Termsarasab et al, 2014 ). Ebrahimi-Fakhari et al (1993) reported that the patients with PRRT2 heterogenous variants commonly exhibited epilepsy and paroxysmal movement disorders (PRRT2-associated paroxysmal movement disorders, RRT2-PxMD) without intellectual delay.…”
Section: Discussionsupporting
confidence: 94%
“…To date, more than 400 patients with 16p11.2 deletions have been reported. Only six of these cases have been reported to have PKD (Dale, Grattan‐Smith, Fung, & Peters, ; Dale, Grattan‐Smith, Nicholson, & Peters, ; Lipton & Rivkin, ; Silveira‐Moriyama et al, ; Termsarasab et al, ; Weber, Kohler, Hahn, Neubauer, & Muller, ). The deletion ranges and phenotypes of these patients with PKD are summarized in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, a 593‐kb deletion at map position B29.5–B30.1 Mb in the proximal region of 16p11.2 was defined as a typical 16p11.2 deletion commonly associated with symptoms of brain developmental abnormalities, while a 220‐kb deletion at map position B28.74–B28.95 Mb in the distal region was defined as an atypical 16p11.2 deletion featured by severe obesity due to the involvement of the SH2B1 gene, which plays a role in leptin and insulin signaling. PKD patients with PRRT2 CNVs all had the proximal 16p11.2 deletions (Dale et al, ; Lipton & Rivkin, ; Silveira‐Moriyama et al, ; Termsarasab et al, ; Weber et al, ). The overlapping region of the deletions contains two known causative genes— PRRT2 and KIF22 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, these patients present multiple congenital abnormalities, developmental delay, epilepsy, autism spectrum disorder, obesity, and psychiatric illnesses 11,[115][116][117][118][119] and also developmental delay, intellectual disability, and/or autism spectrum disorder. 28,30,120,121 Structural mutations at 16p11.2 has been associated to schizophrenia. 122 No clear evidence for genotype-phenotype correlations exists for PKD, BFIE, PKD with IC and HM.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%